1989
DOI: 10.1139/z89-168
|View full text |Cite
|
Sign up to set email alerts
|

The infl1uence of physical clutter and noise on the activity of bats over water

Abstract: To determine why some bats concentrate their activity over calm water rather than turbulent water, we studied the effects of surface clutter and running-water noise on the foraging activity of Myotis lucifugus (little brown bats), which commonly fly within 0.5 m of the water surface, and Eptesicus fuscus (big brown bats), which forage at greater heights, in southwestern Alberta, Canada. In paired experiments over calm water, artificial clutter reduced the activity of M. lucifugus, but not that of E. fuscus, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 14 publications
2
53
2
1
Order By: Relevance
“…By contrast, aerial hawking bats that detect and track insects by echolocation can be attracted by the high prey abundance associated with anthropogenic habitat alterations, such as streetlights alongside roads (Arlettaz et al, 2000;Avila-Flores and Fenton, 2005) or garbage dumps (Kronwitter, 1988). While this might indicate some dichotomy in how bats from different ecological groups deal with human impact, previous playback experiments indicate that in addition to 'passive listening' bats as shown in the present study, aerial hawking species are also affected and deterred by broadband noise (Mackey and Barclay, 1989;Spanjer, 2006;Szewczak and Arnett, 2006). In the course of environmental impact assessments for highway planning, appropriate preventive measures (noise reduction) or compensatory measures (amelioration of alternative bat foraging habitats) will, according to the respective applicable national and international law, have to be considered.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…By contrast, aerial hawking bats that detect and track insects by echolocation can be attracted by the high prey abundance associated with anthropogenic habitat alterations, such as streetlights alongside roads (Arlettaz et al, 2000;Avila-Flores and Fenton, 2005) or garbage dumps (Kronwitter, 1988). While this might indicate some dichotomy in how bats from different ecological groups deal with human impact, previous playback experiments indicate that in addition to 'passive listening' bats as shown in the present study, aerial hawking species are also affected and deterred by broadband noise (Mackey and Barclay, 1989;Spanjer, 2006;Szewczak and Arnett, 2006). In the course of environmental impact assessments for highway planning, appropriate preventive measures (noise reduction) or compensatory measures (amelioration of alternative bat foraging habitats) will, according to the respective applicable national and international law, have to be considered.…”
Section: Discussionmentioning
confidence: 47%
“…Nevertheless, natural noise is likely to affect the foraging efficiency of bats. Behaviour observation and playback experiments suggested that noise from turbulent water could interfere with echo-based prey detection in bats that forage close to, as well as several meters above, water surfaces (von Frenckell and Barclay, 1987;Mackey and Barclay, 1989;Rydell et al, 1999). The artificial broadband noise in our experiments contained higher frequencies than the traffic noise.…”
Section: Influence Of Noise Structurementioning
confidence: 66%
See 1 more Smart Citation
“…Furthermore, calm surface water provides a less cluttered acoustic signal return from the echolocation pulses (Mackey and Barclay 1989;Siemers et al 2001), and there is some evidence, at least for echolocating bats, that activity over calm pools of water is higher than that over fastflowing riffles (von Frenckell and Barclay 1987). Bat activity in a transect from dry woodland savannah to riverine habitat in southern Africa was correlated with insect abundance-both bat activity and insect abundance were higher in riverine habitat (Rautenbach et al 1996) suggesting that bats were attracted to this habitat because of the feeding opportunities it provided.…”
Section: Bodies Of Water As a Foraging Habitatmentioning
confidence: 99%
“…Some species (e.g., M. daubentonii), adapted to hawking insects just above the water or even gaffing them directly from its surface (Jones and Rayner 1988;Todd and Waters 2007), benefit from an acoustic mirror effect (Siemers et al 2005). However, they cannot detect prey if water surface is turbulent, as frequently occurs in shallow and narrow streams (Mackey and Barclay 1989;Rydell et al 1999), or if it is covered by floating vegetation (i.e., pleustophytes) (Boonman et al 1998;Ciechanowski et al 2007). Bats reveal clear microhabitat preferences, dependent on their foraging tactics.…”
Section: Introductionmentioning
confidence: 99%